Nanoparticles of Chitosan Loaded Ciprofloxacin: Fabrication and Antimicrobial Activity - Zahra Sobhani; Soliman Mohammadi Samani; Hashem Montaseri; Elham Khezri (Tabriz University of Medical Sciences, 2017)
Purpose: Chitosan is a natural mucoadhesive polymer with antibacterial activity. In the present study, chitosan (CS) nanoparticles were investigated as a vehicle for delivery of antibiotic, ciprofloxacin hydrochloride. Methods: Ionotropic gelation method was used for preparation chitosan nanoparticles. The effects of various factors including concentration of CS, concentration of tripolyphosphate (TPP), and homogenization rate on the size of nanoparticles were studied. The effects of various mass ratios of CS to ciprofloxacin hydrochloride on the encapsulation efficiency of nanoparticles were assessed. Results: The particles prepared under optimal condition of 0.45% CS concentration, 0.45% TPP concentration and homogenizer rate at 6000 rpm, had 72 nm diameter. In these particles with 1:0.5 mass ratio of CS to ciprofloxacin hydrochloride, the encapsulation efficiency was 23%. The antibacterial activity of chitosan nanoparticles and ciprofloxacin-loaded nanoparticles against E.coli and S.aureus was evaluated by calculation of minimum inhibitory concentration (MIC). Results showed that MIC of ciprofloxacin loaded chitosan nanoparticles was 50% lower than that of ciprofloxacin hydrochloride alone in both of microorganism species. Nanoparticles without drug exhibited antibacterial activity at higher concentrations and MIC of them against E.coli and S.aureus was 177 and 277 µg/ml, respectively. Conclusion: Therefore chitosan nanoparticles could be applied as carrier for decreasing the dose of antibacterial agents in the infections.